2008
DOI: 10.2133/dmpk.23.45
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inducibility of Sulfotransferase and UDP-Glucuronosyltransferase mRNAs by Prototypical Microsomal Enzyme Inducers in Primary Cultures of Human and Cynomolgus Monkey Hepatocytes

Abstract: We investigated the change of the mRNA levels of sulfotransferase and UDP-glucuronosyltransferase isoforms by the prototypical microsomal enzyme inducers rifampicin (Rif), dexamethasone (Dex), and omeprazole (Ome) in primary cultures of cryopreserved human and cynomolgus monkey hepatocytes. Real-time RT-PCR analysis was performed using primers and TaqMan probes. Rif, Dex, and Ome increased SULT2A1 mRNA level in both human and cynomolgus monkey hepatocytes in dose-dependent manner, but not SULT1A1 mRNA level. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…It has been reported that PB is an inducer of GSTA1/2 (Morel et al, 1993) and that OME and RIF are inducers of UGT1A1 (Nishimura et al, 2008). Note that the -fold inductions of these two genes with the three inducers were much lower than those observed with P450s, ranging mostly between 1.5-and 5-fold, with the exception of UGT1A1 induction by PB and OME that reached 7 to 10-fold (Table 1).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It has been reported that PB is an inducer of GSTA1/2 (Morel et al, 1993) and that OME and RIF are inducers of UGT1A1 (Nishimura et al, 2008). Note that the -fold inductions of these two genes with the three inducers were much lower than those observed with P450s, ranging mostly between 1.5-and 5-fold, with the exception of UGT1A1 induction by PB and OME that reached 7 to 10-fold (Table 1).…”
Section: Discussionmentioning
confidence: 72%
“…However only limited studies still exist on the regulation of UGTs in human hepatocytes (Soars et al, 2004;Nishimura et al, 2008). We show that in addition to the major P450s, several phase II enzymes and transporters were modulated by PB, RIF, and/or OME.…”
Section: Discussionmentioning
confidence: 82%
“…Animal models are variable in their relevance for study of these reproductive effects (TaubĂžll et al 2008). Rationale for the use of nonhuman primates, specifically cynomolgus monkeys, as models for the effects of DME induction on steroid reproductive hormone phase II metabolism has been presented (Barbier and BĂ©langer 2003;Nishimura et al 2008). 822 ENNULAT ET AL.…”
Section: Endogenous Reproductive Hormone Effects Associated With Protmentioning
confidence: 99%
“…Isolation of Cynomolgus Monkey Hepatocytes Perfusion of the cynomolgus monkey liver was performed according to the Seglen method 13) with some modifications. 14,15) The hepatocytes obtained were stored in liquid nitrogen until use.…”
Section: Comparison Of Inducibility Of Multidrug Resistance (Mdr)1 Mmentioning
confidence: 99%
“…14,15) Human cell suspensions with viability rates of 90 to 94 as assessed by trypan blue dye exclusion and cynomolgus monkey cell suspensions with viability rates of 80 to 92 as assessed by the same method were used for the experiments. The hepatocytes were used for experiments at 48 h after inoculation.…”
Section: Monolayer Culture Of Human and Cynomolgus Monkey Hepatocytesmentioning
confidence: 99%